Unions, Works Councils and Plant Closings in Germany - John T. Addison; Lutz Bellmann; Arnd Kölling (Institute for the Study of Labor (IZA), 2002)
This paper present paper provides the first results for Germany on the impact of works councils and collective agreements on plant closings, using data from the IAB establishment panel. We find evidence of a robust positive association between works council presence and plant closures. The strictures of collective agreements do not seemingly affect closings. By the same token, and contrary to some recent findings on other aspects of establishment performance, the presence of a collective agreement does not attenuate the impact of local workplace representation on closings. Our analysis does nothing to encourage a sanguine view of recent legislation in Germany that facilitates the formation of works councils and strengthens their codetermination powers.
Keywords: J53; J51; J58; J65; 330; rent seeking; workplace representation; industry/regional collective bargaining; codetermination; plant closings; Liquidation; Marktaustritt; Gewerkschaftlicher Organisationsgrad; Schätzung; Betriebsrat; Schätzung; Deutschland